Konsep Qathlu Perspektif Fiqih Jinayah: Kajian Tentang Pengertian, Dasar Hukum, Macam-Macam, dan Sanksi dalam Islam - Nailatur Rizqiyah; Masti Yanto; Mad Sa’i (INDO PUBLISHING, 2025)
The issue of murder (qathlu) remains a serious problem in various countries. Often, a lack of in-depth understanding of Islamic law related to qathlu leads to misunderstandings or even the misuse of the law. Therefore, this article aims to comprehensively explore the concept of qathlu from the perspective of fiqh jinayah (Islamic criminal jurisprudence). The research method used is library research, which is descriptive and analytical in nature. The data collection procedure was carried out through document analysis. Document analysis was performed using literature studies in the form of books and journal articles related to the topics discussed in this article. It can be concluded that qathlu (murder) refers to an act that results in the loss of another individual’s life, whether the act was intentional or unintentional. Based on the perpetrator’s intent in committing the murder, qathlu is divided into three categories: premeditated murder (al-qathlul ‘amdi), semi-premeditated murder (al-qathl syibhul ‘amdi), and unintentional murder (al-qathlul khata’). As for the sanctions imposed on perpetrators of qathlu from the perspective of fiqh jinayah: First, the sanction for premeditated murder (al-qathlul ‘amdi) consists of the primary punishment of qisas (retribution), a substitute punishment in the form of paying diyat (blood money), and an additional punishment involving the revocation of the right to inherit or receive a bequest from the victim. Second, the sanction for semi-premeditated murder (al-qathl syibhul ‘amdi) involves paying diyat mughallazah (a heavy fine). Third, the sanction for unintentional murder (al-qathlul khata’) consists of paying diyat mukhafafah (a lighter fine).